A New Day for Family Ministry - Olson, Richard P.; Leonard, Joe H. (Rowman & Littlefield Publishers, 1996)
Families are both a great resource to the church's ministry and in great need of the church's ministry. There are tremendous stresses and changes in families. Business as usual simply will not do. This book sketches a road map that will take American families into a new day in family ministry while grappling with day-to-day challenges.